Agricultural legal agreements - Prutis, Stanisław (Przegląd Prawa Rolnego, 2021)
Distinguishing the conceptual category of “agricultural legal agreements” fulfills the ordering function in doctrinal approaches which concern the mechanism of agreement (consensus) in our legal system. I propose to use the term “agricultural legal agreements” to define all consensual legal actions that serve to implement the objectives of agricultural policy (the functional aspect), and have a nature and construction of civil-law contracts or a construction of administrative contracts that are an obligatory form of action for the administering entity. An administrative contract, as a legal form of action of an administrative body, is a specific equivalent of a civil law contract – an action in private law – taken on the grounds of public law regulations. This “counterpart” status results from structural differences between both contracts, therefore all doctrinal classifications of civil law contracts can be applied to administrative contracts, according to their “appropriateness” at best. Agricultural law is that branch of law which in its regulatory function uses both the mechanism of civil law and administrative contracts. Therefore, there is a need for an integrated research on legal contracts in agriculture, which unequivocally speaks for the need for keeping agricultural law separate.